2023
DOI: 10.1172/jci.insight.155448
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxycholesterol exacerbates vascular leak during acute lung injury

Abstract: Cholesterol-25-hydroxylase (CH25H), the biosynthetic enzyme for 25-hydroxycholesterol (25HC), is most highly expressed in the lung, but its role in lung biology is poorly defined.Recently, we reported that Ch25h is induced in monocyte-derived macrophages recruited to the airspace during resolution of lung inflammation and that 25HC promotes Liver X Receptor (LXR)-dependent clearance of apoptotic neutrophils by these cells. Ch25h and 25HC are, however, also robustly induced by lung-resident cells during the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Enzyme responsible for 25-HC biogenesis is mainly the 25-hydroxylase (CH25H), which uses cholesterol and molecular oxygen as substrates and NADPH as a cofactor. This enzyme is expressed at low levels in several cell types, including hematopoietic cells, epithelial, and endothelial cells (ECs), but also in macrophages and lymphoid organs ( 53 , 54 , 55 ) ( Fig. 3 ).…”
Section: Oxysterol Synthesis: Focus On 25-hc Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzyme responsible for 25-HC biogenesis is mainly the 25-hydroxylase (CH25H), which uses cholesterol and molecular oxygen as substrates and NADPH as a cofactor. This enzyme is expressed at low levels in several cell types, including hematopoietic cells, epithelial, and endothelial cells (ECs), but also in macrophages and lymphoid organs ( 53 , 54 , 55 ) ( Fig. 3 ).…”
Section: Oxysterol Synthesis: Focus On 25-hc Productionmentioning
confidence: 99%
“…Besides the role of 25-HC and 7α,25-DHC in immune response, several studies have reported a key role of these oxysterols in lung in response to respiratory infection. In mouse, high expression of Ch25h is observed in resident alveolar macrophages ( 54 ). When respiratory infection is mimicked by injection of LPS, Ch25h expression is induced particularly in pulmonary ECs and alveolar macrophages ( 54 , 104 ) and 25-HC levels are increased in lungs and bronchioalveolar lavage fluids ( 105 ).…”
Section: -Hc As the First Line Of Defense In The Lungsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 25-OHC is overproduced in both human and mouse alveolar MUs as an agonist for the anti-inflammatory nuclear receptor LXR and may play a central role in the pathogenesis and resolution of pulmonary inflammation [62]. However, in lung injury mouse models, 25-OHC sustains the production of proinflammatory cytokines and increases lung injury to a certain extent by inducing LXR-independent ER stress and endothelial leak [63]. On the other hand, LXR activation protects mouse smooth muscle cells from 7-KC-induced cytotoxicity and apoptosis by ABCG1mediated lipid redistribution which hinders the incorporation of 7-KC into the lipid raft microdomains on the plasma membrane [45,64,65].…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…A recent study has revealed that 5,6-EC can activate the cysteinyl aspartate specific proteinase-3/7 (caspase-3/7)mediated apoptotic pathway by inducing mitochondrial membrane potential changes to produce ROS, which ultimately leads to apoptosis in human osteoma cells [116]. It is worthwhile to Produced by MU activation of TLR in response to pathogen invasion and has extensive antiviral activity [28,29] Regulates plasma cell/IgA production [7,41] Regulates the activation of inflammatory bodies by affecting the level of SREBP-2 [35][36][37][38][39] Acts as a ligand to activate nuclear receptors to regulate inflammatory damage after infection [62,63] Mediates the remodeling of cholesterol in the plasma membrane and limits the intracellular transmission of LM and Shigella fowleri Prevents cell damage caused by CDCs [92,98] 7-hydroxycholesterol (7-OHC)…”
Section: 6-ec and Ctmentioning
confidence: 99%